More than roots: revisiting Kantian elements in predictive processing - Laiho Hemmo; Arstila Valtteri (Springer Science and Business Media LLC, 2026)
This paper explores recent suggestions of conceptual affinity between the Predictive Processing (PP) framework and Immanuel Kant’s philosophy. We argue that Kant’s layered cognitive architecture mirrors PP’s hierarchy, particularly in its top-down processing and active construction of experience. Furthermore, both frameworks endorse a version of internalism that emphasizes the mind’s representational mediation of reality rather than direct access to external objects. However, key differences remain, notably Kant’s emphasis on a priori constraints and conscious judgment, contrasted with PP’s probabilistic and subpersonal predictive mechanisms. By highlighting these convergences and tensions, we conclude that PP is not only largely compatible with Kantian themes but constitutes a contemporary variant of Kantianism, reanimating essential insights within a scientific framework.